2003
DOI: 10.1111/1468-2508.t01-1-00003
|View full text |Cite
|
Sign up to set email alerts
|

Patronage, the Pendleton Act, and the Power of the People

Abstract: The conventional wisdom and congressional scholarship find that members of Congress use their public authority to facilitate their reelections (Aldrich 1995; Moe 1990; Parker 1992; Weingast and Marshall 1988). The adoption of the Pendleton Act of 1883 has been cited as another in a long line of examples in which members have “stacked the deck” in their own self‐interests (Johnson and Libecap 1994a). I challenge these pervasive views by presenting evidence that public pressure was an important and frequently ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 11 publications
0
27
0
2
Order By: Relevance
“…Early historic accounts of, in particular, the U.S. case focused on civic reform coalitions mobilizing opposition to the allegedly inefficient and corrupt patronage system and working to secure the election of Congress Members sympathetic to reform (see, for instance, Van Riper, 1958). Societal organizations for reform were complemented by massive public education campaigns to sway public opinion against patronage (Theriault, 2003). The non-partisan press, civil society associations, unions and the middle class all stand to gain from more than a strengthened state with reform: reform advantages the middle (and, at times, upper) class in the competition for public employment while the crumbling of patronage-based party organizations enhances the power of media and collective societal actors in political decision-making (Shefter, 1993).…”
Section: The Demand For Reform Of Patronage Bureaucraciesmentioning
confidence: 99%
“…Early historic accounts of, in particular, the U.S. case focused on civic reform coalitions mobilizing opposition to the allegedly inefficient and corrupt patronage system and working to secure the election of Congress Members sympathetic to reform (see, for instance, Van Riper, 1958). Societal organizations for reform were complemented by massive public education campaigns to sway public opinion against patronage (Theriault, 2003). The non-partisan press, civil society associations, unions and the middle class all stand to gain from more than a strengthened state with reform: reform advantages the middle (and, at times, upper) class in the competition for public employment while the crumbling of patronage-based party organizations enhances the power of media and collective societal actors in political decision-making (Shefter, 1993).…”
Section: The Demand For Reform Of Patronage Bureaucraciesmentioning
confidence: 99%
“…This may or may not be true. Some scholars have found that pressure—either directly from the public or through interest groups—can force government to change, even when it does not want to (Theriault ). Others have found that lawmakers (and by extension the president), in structuring administrative agencies, have the greatest ability to decide what type of access groups will have (Macey ).…”
Section: Lobbyist Influence On Governmentmentioning
confidence: 99%
“…115, February 17, 2009). U.S. Department of the Treasury, "Treasury Secretary Opens Term Opens [sic] With New Rules To Bolster Transparency, Limit Lobbyist Influence in Federal Investment Decisions," press release, January 27, 2009, http://www.treasury.gov/press-center/pressreleases/Pages/tg02.aspx (accessed January 20, 2015 even when it does not want to (Theriault 2003). Others have found that lawmakers (and by extension the president), in structuring administrative agencies, have the greatest ability to decide what type of access groups will have (Macey 1992).…”
Section: Interest Groups Pressure and Representation In Washingtonmentioning
confidence: 99%
“…The constituency's influence on member voting behavior is a well-studied political phenomenon. Various scholars find a moderate to strong relationship between constituency opinion and member behavior (Ansolabehere, Snyder, and Stewart 2001;Bartels 1991;Erikson 1978;Jessee 2009;Kingdon 1973;Theriault 2003Theriault , 2005Theriault , and 2008Wright, Erikson, and McIver 1994). When presidents issue vetoes, they forcefully insert themselves into the policy debate, heighten issue salience, and increase the influence of constituency opinion on member voting behavior.…”
Section: How Constituencies and Electoral Incentives Affect Members' mentioning
confidence: 99%